Observation de la Terre et du Soleil depuis l’espace : vers un changement de paradigme - Philippe Keckhut; Mustapha Meftah; Laurence Croizé (L'Espace Politique)
Satellite platforms positioned around the Earth have made it possible to obtain a global vision of our planet. However, whatever their performance, “traditional” satellites are insufficient to provide the information necessary to understand the mechanisms involved in monitoring climatic hazards, improving weather forecasting and civil and military security. For some two decades, making it possible to answer these new scientific and social questions, new technical vectors have appeared, notably constellations of small satellites and stationary platforms such as drones, gliders and balloons. This development, corresponding to an approach that is both complementary and breaks with the previous approach, promotes, in combination with the tools of artificial intelligence in full development, more numerous and higher quality observations.